Insight into acetylene plasma deposition using molecular dynamics simulations. Issue 1 (4th October 2021) - Brault, Pascal; Ji, Marisol; Sciacqua, Dario; Poncin‐Epaillard, Fabienne; Berndt, Johannes; Kovacevic, Eva
Abstract: Molecular dynamics simulations are carried out for studying the growth and properties of polymers from pure acetylene plasma. A mixture of H, C2 H, and C2 H2 is the initial composition used for running the molecular dynamics simulations. The resulting films are characterized by determining the bond order, [H]/[C] ratio, and simulated infrared spectrum. The latter is qualitatively compared with three different experiments: IR peak identification and positions are recovered. Abstract : Reactive molecular dynamics simulations are able to describe plasma polymer deposition and the resulting film structure. Simulation of the resulting IR spectrum enables comparison with corresponding experiments